BI’AH LUGHOWIYAH (LINGKUNGAN BERBAHASA) DAN PEMEROLEHAN BAHASA (Tinjauan tentang Urgensi Lingkungan Berbahasa dalam Pemerolehan Bahasa) - A. Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2012)
Language is not the individual products in person, but rather a communal social product, in which individuals grow and absorb the rules of language in their community by learning (ta’allum) or mimic (muhâkah). Therefore this is the creation of language the good and the righteous will greatly affect a person’s language acquisition. Humans acquired Language in two ways: 1) the acquisition of language (al lughah legal profit / language acquisition) that are common in children when acquiring the first language or mother tongue of the environment. This ability is acquired unconsciously by communicating directly with the people who use such language, 2) learning languages (language learning / ta ‘allum al lughah) the language skills gained from the processes that occur at the time someone learning a second language did knowingly, after he obtained his first language.